2021
DOI: 10.1371/journal.pntd.0009321
|View full text |Cite
|
Sign up to set email alerts
|

Localized skin inflammation during cutaneous leishmaniasis drives a chronic, systemic IFN-γ signature

Abstract: Cutaneous leishmaniasis is a localized infection controlled by CD4+ T cells that produce IFN-γ within lesions. Phagocytic cells recruited to lesions, such as monocytes, are then exposed to IFN-γ which triggers their ability to kill the intracellular parasites. Consistent with this, transcriptional analysis of patient lesions identified an interferon stimulated gene (ISG) signature. To determine whether localized L. braziliensis infection triggers a systemic immune response that may influence the disease, we pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 74 publications
3
29
0
2
Order By: Relevance
“…The top 12 overrepresented SASP genes were associated with recruitment of inflammatory immune cells (CCL3, CCL8, CXCL1, CXCL11, CXCL13, CXCL8); metalloproteinases (MMP1, MMP10 and MMP3) and inflammatory cytokines (IL‐6, IL‐15 and IL‐1β) (Figure 3b, c and Figure ). In addition, other non‐SASP inflammatory cytokines, chemokines and their receptors such as IFN‐γ ( IFNG ), TNF‐α ( TNF ), IL‐23 ( IL23A ), IL‐15 receptor ( IL15RA ), CXCL10, CXCL9, CCL4 and CCR5 were overrepresented in CL lesions (Figure 3C and Figures ), supporting previous findings [13,14,29,37,39]. As expected, most of the DEGs positively correlated with the predicted relative proportions of analysed cell subsets (Figure 3C).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The top 12 overrepresented SASP genes were associated with recruitment of inflammatory immune cells (CCL3, CCL8, CXCL1, CXCL11, CXCL13, CXCL8); metalloproteinases (MMP1, MMP10 and MMP3) and inflammatory cytokines (IL‐6, IL‐15 and IL‐1β) (Figure 3b, c and Figure ). In addition, other non‐SASP inflammatory cytokines, chemokines and their receptors such as IFN‐γ ( IFNG ), TNF‐α ( TNF ), IL‐23 ( IL23A ), IL‐15 receptor ( IL15RA ), CXCL10, CXCL9, CCL4 and CCR5 were overrepresented in CL lesions (Figure 3C and Figures ), supporting previous findings [13,14,29,37,39]. As expected, most of the DEGs positively correlated with the predicted relative proportions of analysed cell subsets (Figure 3C).…”
Section: Resultssupporting
confidence: 88%
“…Although there are few parasites, their presence in the skin tissue is not correlated to the size of the lesions observed in patients. Recent data show that the lesional parasite load directly correlates with the transcriptional signature of inflammatory, cytotoxic mediators and accumulation of cytotoxic CD8 + T cells [61], and these are the main responsible for the tissue pathology [14,29]. The accumulation of senescent and non‐senescent cells in the cellular infiltrate as well as local inflammation may clarify the correlation observed between the parasites and senescence signature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, no DEGs were identified by RNA-seq in whole blood ( Supplemental Figure 4 and Supplemental Table 2 ), suggesting that unlike CL caused by L . braziliensis ( 21 ), CL due to L . donovani in Sri Lanka is not accompanied by an overt systemic immune response.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study comparing the gene expression profile of primary cutaneous lesions from L. braziliensis-infected patients with or without pentavalent antimony treatment revealed most of the differentially expressed transcripts were correlated with components of cytotoxicity related pathways and parasite load in the skin (39). While another study using RNA-Seq from the same group revealed a consistent and significant myeloid interferon stimulated gene (ISG) signature in skin lesions from L. braziliensis-infected patients (43). Altogether, these studies revealed that the host immune response upregulates transcripts related to both pro-inflammatory and antiinflammatory responses during leishmaniasis (44,45).…”
Section: Introductionmentioning
confidence: 99%